Analisis Penerapan ESD dalam Pembelajaran IPA Daring Pada Masa Pandemi Covid-19 - Mia Aina; Dalimawaty Kadir; Baso Intang Sappaile; Dara Mutiara Aswan; Asita Al Mufida (Jurnal Penelitian Pendidikan IPA, 2023)
Education for Sustainable Development (ESD) is a program designed to achieve sustainable development goals. In the 2013 curriculum, ESD has been used as one of the bases for teaching science to students. However, the existence of the Covid-19 outbreak in Indonesia has had an effect on science learning activities in junior high schools, so that face-to-face learning has been shifted to online learning. This study aims to analyze activities in online learning, the obstacles experienced by teachers and students, and their effectiveness in implementing ESD principles. The method used is descriptive qualitative to describe online learning at one of the Junior High School (SMP) and Islamic Junior High School (MTs) in West Java. The Researchers used data from the analysis of the teacher's lesson plan and semi-structured interviews with 2 teachers and 2 students. Data analysis was performed by reducing data, presenting data, and drawing conclusions. The results show that online learning is less effective in implementing ESD values because the material presented is limited and learning is only one-way (teacher center). Online learning is carried out using WhatsApp, Google Classroom, and e-learning media with obstacles in the form of internet network instability and a lack of student motivation. Therefore, it is hoped that the teacher can use a learning model that is more attractive, student-centered, and can implement the principles of ESD.